Analisis Penerapan E-Government Guna Meningkatkan Kualitas Pelayanan Publik - Afriyanti, Dewi Naluri; Lodan, Karol Teovani; Khairina, Etika (Prosiding, 2024)
The development of communication technology and information currently has a big impact, especially on government agencies. Government with its various forms of institutions is a dynamic forum. Where activities are always developing, they also affect the global environment. Therefore, along with the development of the country, Indonesia is implementing e-Government when facing various challenges and demands to achieve progress and good governance. The application of e-Government is utilizing technology, information, communication to carry out government activities so that they are effective and efficient in public services. This makes it easy to reach and also expands access to information. This article was written using the literature study method. Which the author searches for and obtains from books, articles, journals and the internet.